(untitled) (World Science, 2022)
The study was conducted to determine the amount of contamination such as soot and silicon iron of engine oil and fuel contamination of tractors of Mongolia’s agricultural sector. According this research, tractors were randomly selected for field testing during spring’s sowing and summer and autumn harrowing time, and fuel and oil samples were taken from them with a special vacuum suction according relevant instructions and the amount of contamination was determined in accredited laboratory of Tecenomics Mongolia LLC. According to the test results, fuel contamination increases exponentially and oil contamination increases polynomial, those results depending on the type of agricultural works, and period of the work in the field of the tractors.